Analytical study on the application of earnings management practices in the Algerian business environment from professionals’ perspectives - Ben Chikh, Samir; Khemgani, Badr Ez Zamane; Kouskous, Messaoud (International journal of economic perspectives, 2024)
This study aims at analyzing the methods of earnings management applied in the Algerian environment. It involves a field study on a group of 65 professionals who answer a questionnaire made up of two axes, namely the exploitation of the flexibility in the accounting practices provided for in the financial accounting system, and the earning management practices through the real operational activities and the financial and investment policies. Findings show no statistically significant differences attributed to the experience among the informants regarding the two axes. However, we find statistically significant differences attributed to the specialty among the informants regarding the two axes.